Excision of metastatic breast cancer from sternum and reconstruction in two patients with solitary metastatic spread. Issue 8 (31st August 2020) - Mohamed, Saifullah; Mazhar, Khurum; Osman, Ahmed; Patel, Akshay; Srinivasan, Lakshmi; Ghosh, Shilajit
Abstract: Metastatic breast carcinoma is a relatively common clinical entity. However, the prognosis of oligometastatic and polygometastatic disease differs considerably pertaining to five-year survival. Metastatic breast carcinoma to the sternum has been described as early as 1988. We describe two cases in our institution who presented with solitary sternal metastases with a previous history of treated breast cancer. In both cases, there had been a history of previous left breast cancer treated aggressively with surgical resection and adjuvant oncological therapy and maintenance hormonal therapy. Partial sternectomy or total sternectomy for solitary metastatic sternal deposits is well established with relatively low morbidity and mortality and improvement in quality of life and possible improvement in long-term survival. Furthermore, reconstructive options are inherently dependent on extent of resection performed. These techniques can incorporate the use of sternal plates in order to approximate defects and reinforce the sternum in the setting of partial sternectomy.